2022
DOI: 10.3390/foods11091295
|View full text |Cite
|
Sign up to set email alerts
|

Blanching Effect on the Quality and Shelf-Life Characteristics of Fresh Cowpea Grains [Vigna unguiculata (L.) Walp.]

Abstract: The high perishability of fresh cowpeas impairs its commercialization. Thus, this study aims to determine the temperature–time binomial for blanching fresh cowpea [Vigna unguiculata (L.) Walp] by evaluating the effects of heat treatment and kinetic behavior on the peroxidase (POD) activity and on the physical characteristics (firmness, color, mass gain). A factorial design (3 × 6) with temperature (70, 80, and 90 °C) and time (1, 2, 4, 6, 8, and 10 min) was implemented. Physicochemical, microbiological, and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Pre-treatments have been widely used in different fruits and vegetables to improve their stability for consumption and commercialization and extend the product’s shelf-life. An example of this is the study of Tavares et al [ 1 ], where the blanching of fresh cowpeas contributed to enzymatic inactivation and microbiological control, promoting product conservation. The results showed that the ideal blanching conditions are 70 °C for 4 min, where significant quality losses are minimized, and the shelf-life of the samples is extended by 5 days.…”
mentioning
confidence: 99%
“…Pre-treatments have been widely used in different fruits and vegetables to improve their stability for consumption and commercialization and extend the product’s shelf-life. An example of this is the study of Tavares et al [ 1 ], where the blanching of fresh cowpeas contributed to enzymatic inactivation and microbiological control, promoting product conservation. The results showed that the ideal blanching conditions are 70 °C for 4 min, where significant quality losses are minimized, and the shelf-life of the samples is extended by 5 days.…”
mentioning
confidence: 99%